2017
DOI: 10.1111/mcn.12474
|View full text |Cite
|
Sign up to set email alerts
|

Delivery mode and breastfeeding outcomes among new mothers in Nicaragua

Abstract: Breastfeeding has been shown to benefit infants and mothers. Women who have caesarean deliveries (C-sections) are expected to be less likely to initiate and continue breastfeeding than those who have vaginal deliveries. Given the high rate of C-sections in Nicaragua, the importance of breastfeeding, and the centrality of culture in choices about breastfeeding, this study sought to examine if mode of delivery relates with breastfeeding initiation and exclusivity in Nicaragua.Two hundred fifty mothers were surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
7
14
1
1
Order By: Relevance
“…The same results had been found in our nationally representative samples [19]. A similar observation was also mentioned by several studies [36][37][38][39][32][33][34]. This study found that mothers aged 20-34 years were more likely to provide EIBF to their children than mothers aged 35 years and above.…”
Section: Discussionsupporting
confidence: 91%
“…The same results had been found in our nationally representative samples [19]. A similar observation was also mentioned by several studies [36][37][38][39][32][33][34]. This study found that mothers aged 20-34 years were more likely to provide EIBF to their children than mothers aged 35 years and above.…”
Section: Discussionsupporting
confidence: 91%
“…The nutritional status of mothers was an important predictor of initial breastfeeding, and it was observed that under nourished mothers were more likely to provide their breast milk to their infants than healthy and over nourished mothers, same results had been in our nationally representative samples [18]. Similar observation was also mentioned by several studies [30,[32][33][34]. This study found that highly reproductive mothers (age, 20-34) had more likely to provide EIBF to their children than mothers aged 35 years and above.…”
Section: Discussionsupporting
confidence: 89%
“…The present nding coincided with another Chinese study [29]. But our results was not supported by BDHS survey data conducted in 2014 [18] and a study from Nicaragua [30] showing no signi cant association between EIBF and place of delivery. It was noted that mothers living in poor income were more interested to provide their initial breast milk to their infants than middle incoming family, however BDHS-2014 indicated no signi cant association between EIBF and wealth index [18].…”
Section: Discussioncontrasting
confidence: 63%
“…On the other hand, recent studies in Ireland and UK [114], and Canada [127] reveals that home delivery significantly increased the odds of TIBF and EBF. Another study in Central America showed that mode of delivery does not affect TIBF and EBF [128]. This inconsistency may be due to the difference in socio-economic status and health care services.…”
Section: Time-trend Analysismentioning
confidence: 98%